2007
DOI: 10.1080/14017430701601636
|View full text |Cite
|
Sign up to set email alerts
|

Patients with coronary artery- or chronic obstructive pulmonary disease walk with mechanical inefficiency

Abstract: Both COPD and CAD patients show mechanical inefficiencies when walking compared to healthy controls. Inactivity is a common feature between the two patient groups, whereas the exercise limitations are quite different. These findings indicate that the mechanical inefficiency might primarily be caused by inactivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 21 publications
5
11
0
Order By: Relevance
“…This is similar to values found in patients with coronary artery disease (19.2%) and lower than in healthy controls (24.7%) (32). It could be assumed that patients with schizophrenia walk with mechanical inefficiency.…”
Section: Discussionsupporting
confidence: 89%
“…This is similar to values found in patients with coronary artery disease (19.2%) and lower than in healthy controls (24.7%) (32). It could be assumed that patients with schizophrenia walk with mechanical inefficiency.…”
Section: Discussionsupporting
confidence: 89%
“…The ϵ net values in the present study are similar to values found in patients with coronary artery disease (19.2%) and lower than in healthy controls (24.7%) [22]. Gait deficits in schizophrenia have been reported, with the poorest gait patterns found in patients treated with conventional antipsychotics [1].…”
Section: Discussionsupporting
confidence: 83%
“…The initial ϵ net of 17.3% (MST) and 19.4% (CG) can be considered low and within the range of patients that walk with mechanical inefficiency [8,22]. The ϵ net values in the present study are similar to values found in patients with coronary artery disease (19.2%) and lower than in healthy controls (24.7%) [22].…”
Section: Discussionsupporting
confidence: 78%
“…Patients with COPD have a larger active energy expenditure [35] even though it is well recognized that they are moving less. This is consistent with findings of reduced mechanical efficiency in these patients compared to healthy controls [36], [37]. An activity monitor cannot be expected to incorporate such a complex change in an estimate of energy expenditure, so perhaps greater weight should be placed upon direct monitor outputs (steps, activity counts, vector magnitude units, etc.).…”
Section: Discussionsupporting
confidence: 80%